Towards Green Business Model: Assessment of Digitalpreneur Actor’s Awareness In Managing Business Waste - Ika Feni Setiyaningrum; Diyah Ariyani (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2023)
The development of technology has had an impact on the proliferation of digitalpreneur actors. Technology makes it easy for people to open a business. In general, business people's primary orientation is to profit by minimizing costs. Unfortunately, environmental issues have not become part of the business management considerations of most business actors. The concept of green business is an ideal form in the implementation of the business world. In this study, researchers examine the level of awareness of digitalpreneur actors regarding waste management in their business. This study takes samples from digitalpreneur actors in the Central Java region. The data collection method used a questionnaire with a quota sampling technique. The analysis technique used is descriptive statistics. The result of this study is that most digitalpreneur actors know the importance of sorting waste and depositing the results in a waste bank. However, in reality, many digitalpreneur actors still do not realize that the waste management of their business is not good. Therefore, it is essential to educate and socialize about waste bank to increase literacy on the importance of waste processing.